THE EFFECTIVENESS OF BEDSIDE TEACHING LEARNING METHODS TOWARDS THE SELF-EFFIFACY OF THERAPEUTIC COMMUNICATION IN MIDWIFERY STUDENTS IN CLINICAL PRACTICE - Dwi Rahma Wati; Ova Emilia; Yekti Satriandari; Yoyo Suhoyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: One of the competencies that must be mastered by health workers is therapeutic communication. Effective communication can increase patient satisfaction but on the contrary communication failure can cause poor information exchange, misdiagnosis, decreased participation and stressors in patients, and even death. Poor communication can be caused by low self efficacy. Bedside teaching learning through preseptor modeling can affect self efficacy in communication. The study aimed to determine the effectiveness of bedside teaching learning method towards the self-efficacy of therapeutic communication in midwifery students in clinical practice.Method: This research is a quantitative descriptive study. The research sample was all midwifery students in the fifth semester who had clinical practice at PKU Muhammadiyah Hospital of Gamping, and Queen Latifa Hospital as many as 20 students. The sampling technique used saturated features. The research instrument used SE-12 and the preceptor’sassessment in bedside teaching. The bivariate analysis used paired t-test and independent t-test.Results: The results showed that the self-efficacy analysis of prior and after bedside teaching therapeutic communication in the certified group obtained mean different of 19.50 and those in the non-certified group obtained mean different of 5.13. There were differences, but not statistically significant with p-value of 0.153.Conclusion: Bedside teaching effectively increased the self-efficacy of midwifery student communication taught by certified preceptors compared to non-certified preceptors. The stages of bedside teaching in the certified group had a betterlevel of preceptor competence than the group that had not been certified. Clinical advisors are suggested to follow preceptorscertification to increase knowledge.